Geological evidence for a drought episode in the western Pampas (Argentina, South America) duringthe early–mid 20th century - Tripaldi, Alfonsina; Zárate, Marcelo Arístides; Forman, Steven L.; Badger, Timothy; Doyle, Moira Evelina; Ciccioli, Patricia Lucia (The Holocene)
Drought episodes during the early–mid 20th century were recognized and described in several places around the world, with extreme dry conditions and widespread landscape denudation, like during the famous ‘Dust Bowl’ in North America. However, there is scant documentation of droughts in southern South America, particularly from the Pampas, and none based on the geological record. In this article, we provide clear evidence of aeolian reactivation and sand deposition in some areas of La Pampa and San Luis provinces, western Pampas (Argentina), during early–mid 20th century in response to drier conditions, probably amplified, like historic droughts in North America, by anthropogenic factors (e.g. significant population increase and agriculture expansion into a fragile environment). Evidence includes widespread bare sand blowouts, extensive surfaces with active sand migration, steep dune lee slopes, and sharp crests covered by weak soil development (A/C profile), accompanied by historical documents. Optically stimulated luminescence (OSL) ages on aeolian beds confirm mobilization and sedimentation by wind processes c. 95–60 yr BP. Considering the dominant (over 70%) austral spring–summer precipitation, it is possible the rainfall deficit in western Pampas was linked to positive sea surface temperature (SST) anomalies in the western subtropical South Atlantic Ocean (20–30°S and 30–50° W), according to significant canonical correlation between the precipitation field in subtropical South America and the Atlantic Ocean SST anomalies. Fil: Tripaldi, Alfonsina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires; Argentina Fil: Zárate, Marcelo Arístides. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Ciencias de la Tierra y Ambientales de La Pampa; Argentina Fil: Forman, Steven L. University Of Chicago; Estados Unidos Fil: Badger, Timothy. ...